Global inhibition of reactive oxygen species (ROS) inhibits paclitaxel-induced painful peripheral neuropathy. - Mehmet Fidanboylu; Lisa A Griffiths; Sarah J L Flatters (PLoS ONE)
Paclitaxel (Taxol®) is a widely used chemotherapeutic agent that has a major dose limiting side-effect of painful peripheral neuropathy. Currently there is no effective therapy for the prevention or treatment of chemotherapy-induced painful peripheral neuropathies. Evidence for mitochondrial dysfunction during paclitaxel-induced pain was previously indicated with the presence of swollen and vacuolated neuronal mitochondria. As mitochondria are a major source of reactive oxygen species (ROS), the aim of this study was to examine whether pharmacological inhibition of ROS could reverse established paclitaxel-induced pain or prevent the development of paclitaxel-induced pain. Using a rat model of paclitaxel-induced pain (intraperitoneal 2 mg/kg paclitaxel on days 0, 2, 4 & 6), the effects of a non-specific ROS scavenger, N-tert-Butyl-α-phenylnitrone (PBN) and a superoxide selective scavenger, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPOL) were compared. Systemic 100 mg/kg PBN administration markedly inhibited established paclitaxel-induced mechanical hypersensitivity to von Frey 8 g and 15 g stimulation and cold hypersensitivity to plantar acetone application. Daily systemic administration of 50 mg/kg PBN (days -1 to 13) completely prevented mechanical hypersensitivity to von Frey 4 g and 8 g stimulation and significantly attenuated mechanical hypersensitivity to von Frey 15 g. Systemic 100 mg/kg TEMPOL had no effect on established paclitaxel-induced mechanical or cold hypersensitivity. High dose (250 mg/kg) systemic TEMPOL significantly inhibited mechanical hypersensitivity to von Frey 8 g & 15 g, but to a lesser extent than PBN. Daily systemic administration of 100 mg/kg TEMPOL (day -1 to 12) did not affect the development of paclitaxel-induced mechanical hypersensitivity. These data suggest that ROS play a causal role in the development and maintenance of paclitaxel-induced pain, but such effects cannot be attributed to superoxide radicals alone.